Civilizations in World Politics: Reasons for Clash and Dialogue - M. V. Kharkevich (Vestnik MGIMO-Universiteta, 2015)
Civilizations are not a novel subject of research.Todaytheyareincreasinglypopularbothinaca demicandpoliticalspheres.State and non-state actors talk as if civilizations were real actors of world politics. The article outlines the intellectual map of civilizational research in world politics. It finds three actual and one possible directions of civilizational research, namely: civilizational dynamic, inter civilizational ethics, politics of civilizations and civilizational politics. The author stresses the importance of nonessentialist approach in civilizational dynamics studies, its leader being Peter Katzenstein. The rest of the article is devoted to cultivating the selected research direction. The author proposes to view civilizations as a strategic reference framework rather than a real actor of world politics. These reference frameworks are constructed on religious value basis and detailed in a shared literature corpus. They are heterogeneous and in a constant state of flux. It can be viewed as a continuum with one pole being a fundamentalist state of civilization and the opposite one - post secular state of civilization. The middle ground is occupied by secular civilization. The clash and dialogue are not among civilizations but rather among different states or social groups within and among civilizations. The most conflictual group is a fundamentalist one, its reference framework is totally determined by religious values. Compromise for such a group is impossible. The most cooperative group is post secular one since it is based on dialogue. The author concludes that dialogue is guaranteed among post secular societies within the Christian civilization. Within and among non-Christian civilizations dialogue is possible but not guaranteed.